2008
DOI: 10.1111/j.1365-2699.2008.01907.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Pulsatilla vernalis (L.) Mill. (Ranunculaceae): chloroplast DNA reveals two evolutionary lineages across central Europe and Scandinavia

Abstract: Aim The aim of this study was to test hypotheses regarding some of the main phylogeographical patterns proposed for European plants, in particular the locations of glacial refugia, the post-glacial colonization routes, and genetic affinities between southern (alpine) and northern (boreal) populations.Location The mountains of Europe (Alps, Balkans, Carpathians, Central Massif, Pyrenees, Scandinavian chain, Sudetes), and central European/southern Scandinavian lowlands.Methods As our model system we used Pulsati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 55 publications
8
68
1
Order By: Relevance
“…Phylogeographical studies suggest the presence of a higher diversity of haplotypes in mountain areas compared with those in lowland populations (Fig. 3b), which supports the claim that P. vernalis originated in alpine habitats and subsequently colonized the lowland areas in Central Europe during glacial periods also in Scandinavia following the Last Glacial Maximum (LGM) (Ronikier et al 2008).…”
Section: Multiple Origin and Dynamics Of Refugial Sites: The Case Of supporting
confidence: 67%
See 3 more Smart Citations
“…Phylogeographical studies suggest the presence of a higher diversity of haplotypes in mountain areas compared with those in lowland populations (Fig. 3b), which supports the claim that P. vernalis originated in alpine habitats and subsequently colonized the lowland areas in Central Europe during glacial periods also in Scandinavia following the Last Glacial Maximum (LGM) (Ronikier et al 2008).…”
Section: Multiple Origin and Dynamics Of Refugial Sites: The Case Of supporting
confidence: 67%
“…Genetic data has also shown that the presence of P. vernalis in the lowlands of Central Europe is not only the result of a recent (Holocene) post-glacial colonization from the Alpine refugia (Ronikier et al 2008); it indicates the possibility of an earlier migration from mountain to lowland areas and survival in northern periglacial microrefugia, located between the Alps in the south and the Pleistocene ice sheet in the north. During the early Holocene, the lowland populations from territories located now in the southern Poland and southern Germany might have been the sources of further northward migration (Ronikier et al 2008).…”
Section: Multiple Origin and Dynamics Of Refugial Sites: The Case Of mentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of overlapping latitudinal and altitudinal shifts associated with contraction-expansion cycles, southern refugia became extraordinary arenas for plant evolution that fostered a variety of outcomes including fragmentation, competition, hybridization and speciation (Brochmann & al., 1998;Steen & al., 2000). Most of the phylogeographic and genetic research on European refugia has focused on extinction and recolonization processes in the arctic-alpine flora of northern and central glaciated areas (Abbott & Comes, 2004;Ronikier & al., 2008), the identification of central and southern European refugia (Tribsch & Schönswetter, 2003;Schönswetter & al., 2005), and the pathways of recolonization from such refugia into deglaciated areas (Petit & al., 2003). However, little work has been done on how glaciationdeglaciation cycles affected the plants within the refugia of southern Europe (Kropf & al., 2006(Kropf & al., , 2008Petit & al., 2002;Nieto Feliner, 2011).…”
Section: Introductionmentioning
confidence: 99%